Philosophy of mathematics : structure and ontology - Shapiro, Stewart, 1951- (Oxford University Press, 1997)
This text argues that both realist and anti-realist accounts of mathematics are problematic. It articulates a structuralist approach, arguing that the subject matter of a mathematical theory is not a fixed domain of numbers.